2023
DOI: 10.3389/fped.2022.1064108
|View full text |Cite
|
Sign up to set email alerts
|

Weight management recommendations for youth with Down syndrome: Expert recommendations

Abstract: Youth with Down syndrome (DS) have a higher prevalence of overweight and obesity compared to the general youth population. Due to physiological and cognitive differences observed in youth with DS, weight management recommendations developed for the general population, may not be suitable for youth with DS. However, there are no recent recommendations for weight management in youth with DS. A workgroup of clinicians and researchers with extensive experience working with youth with DS came together to give clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The prevalence of being overweight and/or obese among adults with DS ranges from 23% to 70% 19 . Other studies showed an obesity prevalence rate of 49% among DS youth, compared with 39% in the general youth population, and in a multicenter study, 94% of adults were found to have obesity 20,21 . Risk factors for obesity in this population include hypothyroidism, hypotonia, a lower resting metabolic rate, poor dietary habits, and insufficient physical activity 22 .…”
Section: Common Problems Encountered In Adults With Dsmentioning
confidence: 91%
See 1 more Smart Citation
“…The prevalence of being overweight and/or obese among adults with DS ranges from 23% to 70% 19 . Other studies showed an obesity prevalence rate of 49% among DS youth, compared with 39% in the general youth population, and in a multicenter study, 94% of adults were found to have obesity 20,21 . Risk factors for obesity in this population include hypothyroidism, hypotonia, a lower resting metabolic rate, poor dietary habits, and insufficient physical activity 22 .…”
Section: Common Problems Encountered In Adults With Dsmentioning
confidence: 91%
“…19 Other studies showed an obesity prevalence rate of 49% among DS youth, compared with 39% in the general youth population, and in a multicenter study, 94% of adults were found to have obesity. 20,21 Risk factors for obesity in this population include hypothyroidism, hypotonia, a lower resting metabolic rate, poor dietary habits, and insufficient physical activity. 22 The current screening recommendations to address obesity in adults with DS entail an annual evaluation of body mass index at the primary care setting.…”
Section: Obesitymentioning
confidence: 99%
“…Studies show that youth with DS experience a higher prevalence of overweight and obesity compared to their peers in the general population. Estimates suggest that 49% to 80% of young individuals with DS are overweight or obese, with this number rising to 90% by adulthood [22]. The aetiology of obesity in youth with DS is multifactorial [22].…”
Section: Obesity In Genetic Conditionsmentioning
confidence: 99%
“…Estimates suggest that 49% to 80% of young individuals with DS are overweight or obese, with this number rising to 90% by adulthood [22]. The aetiology of obesity in youth with DS is multifactorial [22].…”
Section: Obesity In Genetic Conditionsmentioning
confidence: 99%
“…Low physical activity levels are known to increase the risk for co‐occurring chronic medical conditions, including osteoporosis and dementia, for which individuals with Down syndrome are at increased risk (Agiovlasitis et al, 2020; Bull, 2020; Chicoine et al, 2021; Oreskovic et al, 2020). In addition, individuals with Down syndrome are at increased risk for medical conditions impacted by physical activity, including respiratory and mental health conditions (Ptomey et al, 2023). Physician counseling on physical activity may be helpful in motivating patients and caregivers to increase physical activity levels in adults with Down syndrome, and support in creating physical activity plans that match with the patient's capacity.…”
Section: Introductionmentioning
confidence: 99%